The modernity of Sanskrit - Sawhney, Simona (University of Minnesota Press, 2009)
Sanskrit texts have usually been discussed either within the frames of anthropology and religious studies or with a veneration that has substituted for analysis. Going beyond such approaches, Simona Sawhney argues that only a literary approach that resists the closure of interpretation can reveal the fragility, ambivalence, and tension that mark the canonical texts. Today we witness, Sawhney contends, the near-total appropriation of Sanskrit literature by Hindu nationalism. The Modernity of Sanskrit challenges this appropriation by exploring the complex work of Rabindranath Tagore, M.K. Gandh.